Perception and reaction of undergraduate critical disability studies students to six short films depicting neuro-advancements. - Salvatore, Chiara; Sami, Sehar; Youssef, Sandra; Schmidt, Markus; Wolbring, Gregor (NanoEthics, 2025)
Advancements in neurosciences and neurotechnologies pose various ethical and social challenges, warranting public/stakeholder engagement. Art, such as short films, can expose audiences to the social aspects of neuro-advancements. The 2019 BIO·FICTION Film Festival, for instance, examined how neurotechnologies shape society, the human body, and mind. Students are one important group of stakeholders, as they are expected to be critical thinkers and change agents. The lived reality of disabled people is impacted by neuro-advancements in many ways. Critical disability studies students are therefore key stakeholders, as their programs and courses encourage them to identify and address social challenges faced by disabled individuals. Therefore, they need to be able to evaluate the social impacts of neuro-advancements. Few studies exist that ascertain the views of critical disability studies students on the social impact of neuro-advancements. Our study sought to amplify the voices of critical disability studies students by analyzing the responses of 89 undergraduates from three courses to six top films from the BIO·FICTION festival. Conducted asynchronously due to COVID restrictions, students watched the films independently and responded to four guiding questions about: a) general thoughts about the films, b) their perceived impact on those watching, c) implications for their anticipated careers involving disabled people, and d) the social impact of neuro-advancements on disabled people. Our findings indicated that the topical (non-)fictional short films effectively prompted students to reflect on the social aspects of neuro-advancements and were well received. However, responses also indicated a need for follow-up discussions – virtual or in-person – to address questions about film content and deepen the discussion and class engagement. Such discussion setups could also inform film festivals aiming to raise awareness about the societal implications of emerging technologies.